Marine environmental monitoring with unmanned vehicle platforms: Present applications and future prospects - Yuan, Shuyun; Li, Ying; Bao, Fangwen; Xu, Haoxiang; Yang, Yuping; Yan, Qiushi; Zhong, Shuqiao; Yin, Haoyang; Xu, Jiajun; Huang, Ziwei; Lin, Jian (The Science of the total environment, 2023)
Basic monitoring of the marine environment is crucial for the early warning and assessment of marine hydrometeorological conditions, climate change, and ecosystem disasters. In recent years, many marine environmental monitoring platforms have been established, such as offshore platforms, ships, or sensors placed on specially designed buoys or submerged marine structures. These platforms typically use a variety of sensors to provide high-quality observations, while they are limited by low spatial resolution and high cost during data acquisition. Satellite remote sensing allows monitoring over a larger ocean area; however, it is susceptible to cloud contamination and atmospheric effects that subject the results to large uncertainties. Unmanned vehicles have become more widely used as platforms in marine science and ocean engineering in recent years due to their ease of deployment, mobility, and the low cost involved in data acquisition. Researchers can acquire data according to their schedules and convenience, offering significant improvements over those obtained by traditional platforms. This study presents the state-of-the-art research on available unmanned vehicle observation platforms, including unmanned aerial vehicles (UAVs), underwater gliders (UGs), unmanned surface vehicles (USVs), and unmanned ships (USs), for marine environmental monitoring, and compares them with satellite remote sensing. The recent applications in marine environments have focused on marine biochemical and ecosystem features, marine physical features, marine pollution, and marine aerosols monitoring, and their integration with other products are also analysed. Additionally, the prospects of future ocean observation systems combining unmanned vehicle platforms (UVPs), global and regional autonomous platform networks, and remote sensing data are discussed. [Display omitted] •Presented the state-of-the-art of available unmanned vehicle platforms technology•Analysed unmanned vehicle platforms applications in marine environments monitoring•Discussed the challenging and the of synergistic application of multiple platforms